2022
DOI: 10.1111/clr.13998
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants in dentate primary and secondary Sjögren's syndrome patients: A multicenter prospective cohort study

Abstract: Objectives: To prospectively assess the clinical performance and patient-reported outcomes of dental implants in dentate patients with primary and secondary Sjögren's syndrome (pSS and sSS, respectively) compared to patients without SS. Materials and Methods: Thirty-seven implants were placed in 17 patients with pSS/ sSS and 26 implants in 17 non-SS patients to replace missing (pre)molars. Clinical performance, marginal bone-level changes, patient satisfaction, and oral health-related quality of life (OHRQoL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Several studies have shown promising results for dental implants in patients with Sjögren's syndrome. These studies report high implant survival rates, ranging from 97% [24] to 100% [25], for complete-arch implant-supported restorations. However, it's important to note that the longest follow-up period in these studies was 36-57.6 months [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown promising results for dental implants in patients with Sjögren's syndrome. These studies report high implant survival rates, ranging from 97% [24] to 100% [25], for complete-arch implant-supported restorations. However, it's important to note that the longest follow-up period in these studies was 36-57.6 months [10].…”
Section: Discussionmentioning
confidence: 99%
“…Primary Sjögren's syndrome (pSS) and secondary SS (sSS) represent a spectrum of autoimmune disorders that primarily affect the salivary and lacrimal glands, culminating in symptoms such as dryness syndrome. 1 In clinical practice, the precise and rapid diagnosis of pSS and sSS holds paramount significance in formulating effective therapeutic strategies. In recent years, salivary gland ultrasonography (SGUS) and shear wave elastography (SWE), among other imaging modalities, have increasingly attracted attention, offering novel perspectives for the diagnosis of SS.…”
Section: Introductionmentioning
confidence: 86%
“…Primary Sjögren's syndrome (pSS) and secondary SS (sSS) represent a spectrum of autoimmune disorders that primarily affect the salivary and lacrimal glands, culminating in symptoms such as dryness syndrome 1 . In clinical practice, the precise and rapid diagnosis of pSS and sSS holds paramount significance in formulating effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%